Evaluation of speech-based HMI concepts for information exchange tasks: A driving simulator study. (September 2015) - Hofmann, Hansjörg; Tobisch, Vanessa; Ehrlich, Ute; Berton, André
Abstract : Highlights: We compare different speech-based in-car HMI concepts in a driving simulator study. The HMI concepts are evaluated in terms of usability and driver distraction. The comparison of speech dialog strategies revealed only differences in usability. The use of a GUI impaired the driving performance and raised gaze-based distraction. An avatar does not additionally raise driver distraction but is not accepted by users. Abstract: Due to the mobile Internet revolution, people tend to browse the Web while driving their car which puts the driver's safety at risk. Therefore, an intuitive and non-distractive in-car speech interface to the Web needs to be developed. Before developing a new speech dialog system (SDS) in a new domain developers have to examine the user's preferred interaction style and its influence on driving safety. This paper reports a driving simulation study, which was conducted to compare different speech-based in-car human–machine interface concepts concerning usability and driver distraction. The applied SDS prototypes were developed to perform an online hotel booking by speech while driving. The speech dialog prototypes were based on different speech dialog strategies: a command-based and a conversational dialog. Different graphical user interface (GUI) concepts (one including a human-like avatar) were designed in order to support the respective dialog strategy the most and to evaluate the effect of the GUI on usability and driver distraction. The results show that only few differences concerning speech dialog quality were found when comparing the speech dialog strategies. The command-based dialog was slightly better accepted than the conversational dialog, which seems to be due to the high concept error rate of the conversational dialog. A SDS without GUI also seems to be feasible for the driving environment and was accepted by the users. The comparison of speech dialog strategies did not reveal differences in driver distraction. However, the use of a GUI impaired the driving performance and increased gaze-based distraction. The presence of an avatar was not appreciated by participants and did not affect the dialog performance. Concerning driver distraction, the virtual agent did neither negatively affect the driving performance nor increase visual distraction. The results implicate that in-car SDS developers should take both speaking styles into consideration when designing an SDS for information exchange tasks. Furthermore, developers have to consider reducing the content presented on the screen in order to reduce driver distraction. A human-like avatar was not appreciated by users while driving. Research should further investigate if other kinds of avatars might achieve different results.